Búsqueda de inhibidores de serina proteasas en glándulas accesorias del sistema reproductor masculino - Zalazar, Lucia (2012)
Serine protease inhibitors modulate sperm physiolo-gy through unknown mechanisms. Redundancy of molecules bearing the same activity within the male duct denotes their significance. In order to characte-rize the population of this kind of inhibitors in ac-cessory glands of the male duct, different approaches were employed to search for serine protease inhibitors in male mice tissues. Tissues with the highest acti-vities were selected from extracts enriched in tryp-sin inhibitor activity and sperm protease inhibitor activity. Proteomic tools as affinity chromatography and 1D and 2D electrophoresis followed by mass spectrometry were performed on seminal vesicle and epididymis fractions. These methodologies allowed us to identify SVS IV and SPINK3 in seminal vesi-cle and PI16 in epididymis. On the other hand, in silico search for serine protease inhibitors with pre-dicted or demonstrated expression within the male duct of Mus musculus was performed using 4 data-bases. Twenty trypsin/chemotrypsin inhibitors were found and they were classified according to their fa-milies (Merops) or their Pfam domains. The results obtained by both strategies were complementary.